Better Potato for a Better Life: Reducing Food Insecurity and Dependence on Cereals in Amhara Oromia, Tigray and SNNP regions of Ethiopia - International Potato Center (2016)
Unmanned Aerial Vehicle (UAV)-based remote sensing technology is a game changer in the gathering of agricultural statistics data. Relatively low-cost platforms, coupled with high quality sensors and sophisticated-yet-user-friendly processing techniques allows gathering of accurate crop statistics data at large extent, with minimal effect of clouds.